2018
DOI: 10.3390/membranes8010004
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Scale-up Tool for Pervaporation Processes

Abstract: In this study, an engineering tool for the design and optimization of pervaporation processes is developed based on physico-chemical modelling coupled with laboratory/mini-plant experiments. The model incorporates the solution-diffusion-mechanism, polarization effects (concentration and temperature), axial dispersion, pressure drop and the temperature drop in the feed channel due to vaporization of the permeating components. The permeance, being the key model parameter, was determined via dehydration experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This effect is known to be the coupling between water and organics permeance due to swelling of the membrane. [51] Thus, it can be concluded that DBP incorporated PSSAMA/NaAlg membranes are highly selective toward water.…”
Section: Swelling Studymentioning
confidence: 97%
“…This effect is known to be the coupling between water and organics permeance due to swelling of the membrane. [51] Thus, it can be concluded that DBP incorporated PSSAMA/NaAlg membranes are highly selective toward water.…”
Section: Swelling Studymentioning
confidence: 97%
“…Most likely, the high-added value of the produced esters will encourage membrane researchers to carry out further developments in the field. Similarly, the use of PV in the production of other interesting products, such as biodiesel, can also motivate the expansion of its application, even though its implementation, design, scale-up, and optimization represent current challenges …”
Section: Concluding Outlookmentioning
confidence: 99%
“…Similarly, the use of PV in the production of other interesting products, such as biodiesel, can also motivate the expansion of its application, 102 even though its implementation, design, scale-up, and optimization represent current challenges. 113 The design strategies for the development of new nanomaterials (e.g., MOFs) will play a crucial role in the preparation of novel MMMs. For instance, the preparation of dual-purpose materials would be welcome, as these species can also function as a catalyst, making them an efficient tool for process intensification.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…Modeling is well established for smaller molecules in the chemical industry by chemical engineering personnel educated and trained in applying those methods. Availability of models and data, either by in-house data-bases or by experimentally standardized setups enable predictive process simulation in order to reduce experimental efforts in process design [47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%